Small extracellular vesicles deliver osteolytic effectors and mediate cancer‐induced osteolysis in bone metastatic niche - Qinyu Ma; Mengmeng Liang; Yutong Wu; Ce Dou; Jianzhong Xu; Shiwu Dong; Fei Luo (Journal of Extracellular Vesicles, 2021)
Abstract Extracellular vesicles (EVs) play critical roles in regulating bone metastatic microenvironment through mediating intercellular crosstalks. However, little is known about the contribution of EVs derived from cancer cells to the vicious cycle of bone metastasis. Here, we report a direct regulatory mode between tumour cells and osteoclasts in metastatic niche of prostate cancer via vesicular miRNAs transfer. Combined analysis of miRNAs profiles both in tumour‐derived small EVs (sEVs) and osteoclasts identified miR‐152‐3p as a potential osteolytic molecule. sEVs were enriched in miR‐152‐3p, which targets osteoclastogenic regulator MAFB. Blocking miR‐152‐3p in sEVs upregulated the expression of MAFB and impaired osteoclastogenesis in vitro. In vivo experiments of xenograft mouse model found that blocking of miR‐152‐3p in sEVs significantly slowed down the loss of trabecular architecture, while systemic inhibition of miR‐152‐3p using antagomir‐152‐3p reduced the osteolytic lesions of cortical bone while preserving basic trabecular architecture. Our findings suggest that miR‐152‐3p carried by prostate cancer‐derived sEVs deliver osteolytic signals from tumour cells to osteoclasts, facilitating osteolytic progression in bone metastasis.